Insights Into Coronary Artery Lesions in Kawasaki Disease - Zhang, Danfeng; Liu, Lingjuan; Huang, Xupei; Tian, Jie (Frontiers in Pediatrics, 2020)
This review summarizes recent advances in understanding of the development of coronary arteritis in Kawasaki disease. Kawasaki disease is the most common cause of acquired heart disease among children characterized with coronary artery abnormalities, which can cause myocardial ischemia, infarction and even death. The pathogenic factors of Kawasaki disease and the pathological process of coronary artery disease are not clear at present, which brings challenges to the prevention and treatment of the disease. The treatment of Kawasaki disease focuses mainly on timely administration of intravenous immunoglobulin and aspirin. However, the management of patients who do not respond to this standard therapy remains challenging，which，as a result, coronary artery lesions still occur in some patients and affect their quality of life. In this review, we will discuss the update research data of Kawasaki disease coronary artery lesions.